Scholarship Talk: Meraih Pendidikan Tinggi melalui Beasiswa Bergengsi - Alpiansah, Restu; Nur Fitriyah; Bambang (Insan Kreasi Media, 2023)
Education is an essential component in determining one's future. Individuals, especially university students, want to get a higher and improved degree of education. College students should be provided with access to information on scholarships in order to explore exceptional opportunities offered by international schools. This content is sourced from the talk shows conducted at Universitas Mataram. Around 300 students participated in the live discussion event to gather information on scholarships in Australia and many European countries, such as Poland, France, and Germany. This article aims to offer motivation and information about an international scholarship opportunity for persons who have successfully obtained their bachelor's degree. The outcome of this community activity is that participants have a comprehensive understanding of the right selection of scholarships and the necessary processes involved in the scholarship selection process.